Ureteric orifice obstruction by catheter balloon Post-TURP: A rare cause of obstructive uropathy - Kirby R. Qin; Luke Gibson; Todd G. Manning; Kapil Sethi; Damien Bolton (Urology Case Reports, 2022)
A 50-year-old male underwent small volume TURP for median lobe prostatic hypertrophy. Post-procedure, a 3-way urethral catheter was placed. He subsequently developed flank pain, anuria and creatinine rise. CT demonstrated bilateral obstructive uropathy.In the absence of obstructing lesions, it was suspected that the catheter balloon may have caused obstruction of bilateral ureteric orifices. Balloon deflation (from 30 to 10 mL) and catheter repositioning resulted in rapid resolution of pain and resumption of urine output.Urologists should consider the catheter balloon as a cause of obstructive uropathy, especially after procedures where normal trigonal anatomy is disrupted.